Analogs of human genetic skin disease in domesticated animals - Justin Finch, MD; Stephanie Abrams, DVM; Amy Finch, MBA (Wolters Kluwer, 2017)
Genetic skin diseases encompass a vast, complex, and ever expanding field. Recognition of the features of these diseases is important to ascertain a correct diagnosis, initiate treatment, consider genetic counseling, and refer patients to specialists when the disease may impact other areas. Because genodermatoses may present with a vast array of features, it can be bewildering to memorize them. This manuscript will explain and depict some genetic skin diseases that occur in both humans and domestic animals and offer a connection and memorization aid for physicians. In addition, we will explore how animal diseases serve as a model to uncover the mechanisms of human disease.The genetic skin diseases we will review are pigmentary mosaicism, piebaldism, albinism, Griscelli syndrome, ectodermal dysplasias, Waardenburg syndrome, and mucinosis in both humans and domesticated animals.